Emission of short-lived halocarbons by selected tropical marine phytoplankton / Lim Yong Kian - Lim, Yong Kian (2017)
Biogenic volatile halocarbons contribute free halogen radicals to the troposphere and stratosphere, and may play a role in the catalytic destruction of the ozone layer. The contributions and significant impacts of biogenic halocarbon emissions from the tropics are relatively unknown and are of particular interest due to the prevalence of strong convective forces at the tropics and climate change. Of the marine biogenic sources, the marine microalgae (phytoplankton) inhabiting the oceans that cover 70% of the Earth’s surface, make them a significant source of the short-lived halocarbons. A change in the environment may affect the emission of halocarbons. In this study, the effects of life-stage and irradiance were investigated. Using controlled laboratory experiments, three selected tropical marine phytoplankton were investigated for emission of halocarbons. Three phytoplankton species were grown in flask cultures and sampled for halocarbon emissions during different growth stages of the batch cultures. Growth was estimated using chlorophyll-a and cell number. Halocarbons were measured using a two-syringe collection system followed detection using a GC-MS equipped with a purge and trap system. The phytoplankton were found to emit a suite of short-lived halocarbons, namely CHBr3, CH3I, CHCl3, CHBr2Cl and CH2Br2 at different growth phases. Amphora sp. UMACC 370 was shown to be a stronger halocarbon emitter, especially CH3I (10.55 – 64.18 pmol mg-1 day-1), than the other two taxa, Synechococcus sp. UMACC 371 and Parachlorella sp. UMACC 245 (1.04 – 3.86 pmol mg-1 day-1 and 0 – 2.16 pmol mg-1 day-1, respectively). CH3I has significantly (p<0.05) higher emission rate compared to the other detected compounds. Results show that the emissions of detected short-lived halocarbons are species- and growth phase-dependent, highlighting the importance of considering cell physiological conditions when determining gas emission rates. Chlorophyll-a and cell density normalized to emission rate of all five compounds were found to be highly correlated (p<0.01). The cultures were also exposed to a range of irradiance, 0, 40 and 120 μmol photons m-2 s-1. The photosynthetic performance (Fv/Fm, maximum quantum yield) of the cultures when exposed to the range of irradiance was used as an indicator of algal cell stress from photosynthesis. Fv/Fm was measured using the Water Pulsed Amplitude Modulated Fluorometer (PAM). Exposure to 120 μmol photons m-2 s-1 for 12 hours produced significant (p<0.05) decrease in Fv/Fm and increase in halocarbon emissions, especially the release of CH3I by Amphora sp. UMACC 370. The net changes of Fv/Fm, however, were weakly correlated to the significant (p<0.05) changes in overall emission of the five compounds, suggesting that halocarbon emission triggered from oxidative cell stress at higher irradiance may not be directly linked to photosynthesis but instead to mitochondrion respiration, nutrient limitation or a change in lipid composition within the cell membrane.